Altered Gene Regulatory Networks Are Associated With the Transition From C3 to Crassulacean Acid Metabolism in Erycina (Oncidiinae: Orchidaceae) - Heyduk, Karolina; Hwang, Michelle; Albert, Victor; Silvera, Katia; Lan, Tianying; Farr, Kimberly; Chang, Tien-Hao; Chan, Ming-Tsair; Winter, Klaus; Leebens-Mack, Jim (Frontiers in Plant Science, 2019)
Crassulacean acid metabolism (CAM) photosynthesis is a modification of the core C3 photosynthetic pathway that improves the ability of plants to assimilate carbon in water-limited environments. CAM plants fix CO2 mostly at night, when transpiration rates are low. All of the CAM pathway genes exist in ancestral C3 species, but the timing and magnitude of expression are greatly altered between C3 and CAM species. Understanding these regulatory changes is key to elucidating the mechanism by which CAM evolved from C3. Here we use two closely related species in the Orchidaceae, Erycina pusilla (CAM) and Erycina crista-galli (C3), to conduct comparative transcriptomic analyses across multiple time points. Clustering of genes with expression variation across the diel cycle revealed some canonical CAM pathway genes similarly expressed in both species, regardless of photosynthetic pathway. However, gene network construction indicated that 149 gene families had significant differences in network connectivity and were further explored for these functional enrichments. Genes involved in light sensing and ABA signaling were some of the most differently connected genes between the C3 and CAM Erycina species, in agreement with the contrasting diel patterns of stomatal conductance in C3 and CAM plants. Our results suggest changes to transcriptional cascades are important for the transition from C3 to CAM photosynthesis in Erycina.